Exploring the Challenges for Teacher Educators - Goh, Pauline Swee Choo; Wong, Kung Teck (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Teacher competence is recognised as an important requisite to improve students‟ academic performance and their experiences of schooling. Although proponents of standard-based competency have welcomed its introduction, this article argues that standard-based competency poses significant challenges for teacher educators as they set out to train new teachers to begin teaching in ways that are congruent to the standards. The Malaysian government hopes that by initiating standards by which teachers are to be appraised upon, will in turn effect changes in how they are prepared. However, less understood are the challenges it presents for the teaching institutions. This article presents various challenges (and possibilities) for teacher educators. Although the article lacks empirical base for examining these issues, it offers instead a logical analysis based on the authors‟ own (and others‟) experiences to illuminate the issues.